Factors that Influence the Speed of Occurence of Senile Cataracts in South Sumatra - Imaniar Kesuma; Anang Tribowo; Erial Bahar (Sriwijaya Journal of Medicine, 2020)
Introduction. Cataracts are any condition of opacity in the lens that can occur due to the hydration (fluid addition) of the lens, the lens protein denaturation or the consequences of both. Factors that can affect the development rate of the opacity of the lens such as diabetes mellitus, hypertension, certain medications, the B ultraviolet rays from sunlight, toxic effects of smoking, alcohol, less vitamin E, and chronic inflammation in the eyeball.Methods. The type of research is observational analytical with a cross-sectional design. This study was held in August to December in 2019 in Eye hospital in South Sumatra with sampling as many as 234 patients from the medical record. Data is processed using SPSS. The Chi-square test is conducted to determine the relationship of factors that affect the rate of senile cataract in Eye Hospital in South Sumatera Province. Results. From 234 patients, as many as 177 patients (75.6%) with mature cataract and 57 patients (24.4%) with immature cataract. There is no meaningful relation between senile cataract and hypertension (p = 0,068; OR = 1,084; 95% CI = 0,589-1,995). There is no meaningful relation between senile cataract and diabetes mellitus (p = 1.808; OR = 1,876; 95% CI = 0,741-4,747). There is no meaningful relation between senile cataract and gender (p = 0.51; OR = 0,933; 95% CI = 0,514-1,696). There is no meaningful relation between the senile cataract and age (p = 0,784; OR = 1,319; 95% CI; 0,714-2,437).Conclusion. There is no significant relationship between senile cataract occurence, hypertension, diabetes mellitus, gender and age.